Imprinting of Local Metallic States into VO2 with Ultraviolet Light. (18th July 2016) - Zhang, Hai‐Tian; Guo, Lu; Stone, Greg; Zhang, Lei; Zheng, Yuan‐Xia; Freeman, Eugene; Keefer, Derek W.; Chaudhuri, Subhasis; Paik, Hanjong; Moyer, Jarrett A.; Barth, Michael; Schlom, Darrell G.; et al.
Abstract : Materials exhibiting electronic phase transitions have attracted widespread attention. By switching between metallic and insulating states under external stimuli, the accompanying changes in the electrical and optical properties can be harnessed in novel electronic and optical applications. In this work, a laterally confined conductive pattern is inscribed into an otherwise insulating VO2 thin film using ultraviolet light, inducing an almost four orders of magnitude decrease in electrical resistivity of the exposed area. The metallic imprint remains in VO2 after ultraviolet light exposure and can be completely erased by a short low temperature anneal. The ability to optically pattern confined metallic structures provides new opportunities for reconfigurable photonic and plasmonic structures, as well as re‐writable electric circuitry. Abstract : A laterally confined conductive pattern is inscribed into an otherwise insulating VO2 matrix using ultraviolet light, with almost four orders of magnitude decrease in electrical resistivity. The conductive pattern is persistent and can be completely erased by a short annealing. Optical patterning of locally confined metallic structures provides new opportunities in photonics, plasmonics and electronics, such as reconfigurable bottom electrode.